Neurogenic Factors in the Development of Hip-Spine Syndrome (Review) - Zaiets, V.B.; Osadchuk, Т.І.; Kalashnikov, O.V.; Sulyma, O.М. (TERRA ORTHOPAEDICA, 2021)
Summary. Complaints of pain in the buttocks, hip, knee, and lameness are very common among patients with both degenerative changes in the hip joint and the lumbar spine. Failure to pinpoint the source of pain leads to ineffective treatment. Degenerative stenosis of the transverse spine also manifests itself as pain in the extremities and limitation in walking. This is the most common indication for spinal surgery over the age of 65. Before choosing a treatment option for coxarthrosis, it is necessary to take into account the need for intervention at the level of the lumbosacral spine. In the early stages of the development of pathology, preference should be given to active treatment tactics. It is necessary to inform the category of patients with such clinic of damage to the hip joints and spine about the possibility of increased pain after surgery on only one segment and about the probability of surgery on another segment of the biomechanical triangle at the next stage.